Enforced Par Remittance Under the Federal Reserve System - Warne, Colston E. (Quarterly Journal of Economics, 1922)
Introductory. The early development of collections, 275. — The effect of the Federal Reserve Act, 276. — The par remittance plan of 1916, 277. — The Hardwick Amendment and its interpretation by the Federal Reserve Board, 281. — The development of opposition, 283. — The outlook for the future, 286.